Assessing ageist behaviors of Indonesian adult persons using the Relating to Older People Evaluation (ROPE) survey - Bahtiar, Bahtiar (Fakultas Kedokteran, 2021)
Ageism is one of the abandoned psychosocial problems that adult persons were doing age discrimination to the elderly. This study is to describe the prevalence of ageist behaviors amongst adult persons in Makassar city, Indonesia. The method was used a cross-sectional survey design. The Relating to Older People Evaluation (ROPE) survey has been used as an instrument to assess ageist behaviors. One hundred adult persons responded (response rate (RR) 100%). Positive ageist behaviors show that respondents hold doors open for elderly because of their age (93%), enjoy conversations with elderly because of their age (99%), and ask an elderly for advice because of their age (98%). Negative behaviors such as talking louder or slower to old people because of their age (95%), use simple words when talking to old people (99 %), and when an old person has an ailment, they may said, 'that's normal at your age' (96%). Adult persons report engaging in ageist behaviors that potentially harm the mental health of the elderly. This survey can be a reference to solve negative behaviors for older people.